HAMBATAN DALAM IMPLEMENTASI KURIKULUM 2013 REVISI PADA PEMBELAJARAN DARING BAHASA JEPANG TINGKAT SMA DI KABUPATEN KUANTAN SINGINGI - Resva Romyanti; Merri Silvia Basri; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research contains explanations and elaborations regarding the obstacles or challenges faced by Japanese language teachers or instructors, when using the revised 2013 curriculum during online learning when the co-19 pandemic occurred. This research was conducted with the aim of identifying what problems teachers face while implementing the revised 2013 curriculum in schools when teaching online using the 5M scientific approach in the learning process and describing how teachers solve problems that occur in implementing the revised 2013 curriculum at the implementation of Japanese language online learning at a senior high school level. This research was conducted using a qualitative approach method, conducted with full interviews with respondents to find out firsthand the complex problems experienced in social situations that occurred when respondents were carrying out the process of learning Japanese during a pandemic. From interviews obtained data that has been processed and analyzed, and some results can be drawn that the obstacles experienced by teachers include not being able to control students directly when observing scientific approaches, problems implementing strategies to encourage students to ask questions, obstacles when associating, obstacles guiding students to analyze the data and several other obstacles which will be explained in more detail in the results and discussion chapter. The obstacles experienced by teachers in implementing high school Japanese online learning in Kab. Kuantan Singingi is a new situation for teachers. Even so, the teacher still tries to address obstacles so that the learning process continues to run well.Key Words: Challenges, 2013 Curriculum, Japanese Language Online Learning